Happier and further by going together: The importance of software team behaviour during the COVID-19 pandemic. (November 2021) - Marinho, Marcelo; Amorim, Luís; Camara, Rafael; Oliveira, Brigitte Renata; Sobral, Marcos; Sampaio, Suzana
Abstract: The COVID-19 pandemic, and the associated move to remote work and the resulting changes to the normal work routine, have introduced a plethora of new difficulties and challenges for software developers. Recent research has focused on the impact of the COVID-19 pandemic on the developer's wellness, productivity, team collaboration, job satisfaction, and work-life balance. However, research exploring the association between these feelings and team behaviour during such a crisis period has not been previously developed. Moreover, previous research has indicated that organisations are still struggling to understand the pandemic and its relationship with both team behaviour and developer feelings. To address this gap, we analysed how COVID-19 influences a developer's happiness and their feelings of (un)happiness associated with the team's behaviour during the COVID-19 pandemic. A state-of-the-art analysis helped to design a scale that we used in a cross-sectional study of 102 software developers. To test the proposed hypotheses, we conducted exploratory factor analysis and principal component analysis. Our results highlight that happiness positively influences a team's behaviour and that unhappiness negatively affects their work results and productivity. These findings provide software companies and organisations with a better understanding of the importance of team behaviour on individual happiness during crises. These results provide information that managers and companies can use to mitigate potentially negative effects. Highlights: Software developer feelings are affected by the team's behavior during COVID19 pandemic. Roadmap for software practitioners to explore feelings, in order to improve employee well-being and group performance. Promoting positive feelings in a crisis may reduce unhappiness's feelings. Feelings associated with happiness positively influence the team's behavior. Feeling of unhappiness negatively affects the work results and productivity.